Invisible man : Gordon Parks and Ralph Ellison in Harlem - Raz-Russo, Michal; Art Institute, Chicago; Callahan, John, F.; Cloutier, Jean-Christophe; Druick, Douglas; JR.; Kunhardt, Peter, W.; Witkovsky, Matthew, S. (Göttingen : Steidl; the Gordon Parks Foundation, 2017)
Parks, Gordon ; Elisson, Ralph
Invisible man : Gordon Parks and Ralph Ellison in Harlem, Art Institute, Chicago, May 21-August 28, 2016
boek
Keywords: PARKS G; ELLISON R